Examining the functionality of peripheral vision: From fundamental understandings to applied sport science - Vater, C.; Kredel, R.; Hossner, E.-J. (Current Issues in Sport Science, 2017)
In sports, it is important not only to locate gaze on the right location to utilize the high acuity of foveal vision, but also to attend to other objects in the environment without looking directly at them, accordingly, using peripheral vision. Peripheral vision becomes especially important if, for example, the processing of information from more than one location (e.g. players) is decisive in making accurate decisions. Since such decisions generally must be made under high spatio-temporal demands, costly eye-movements might be advantageously avoided by using peripheral vision for information pick-up from multiple cues. In a series of studies, we aimed to translate the demands found in sports and to investigate the functionality of peripheral vision in a well-controlled experimental paradigm, the multiple object tracking (MOT) task. MOT was implemented in a dual task, along with an additional event-detection task. The present article first presents an overview of sport-specific studies focusing on the functionality of peripheral vision and following, summarizes a series of three published MOT studies. These studies show that peripheral vision is used for simultaneous target monitoring and target-change detection and that visual and attentional demands affect gaze anchoring and change-detection rates. Results also reveal a dysfunctionality of saccades, and further suggest an event- and distance-optimized gaze-anchoring position. In the final portion of this article, we derive specific applications for future sports-specific research. Specifically, we suggest to: (a) use dual-task situations in sport-specific settings, such as monitoring multiple players in soccer and playing a pass at specific moments, (b) investigate the costs of saccades in sports situations with high spatio-temporal demands, as in martial arts, and finally, (c) manipulate attentional and visual demands. For each of these avenues of research, we sketch sports-specific experiments currently being conducted in our research group.